Students’ Ability in Comprehending Vocabularies in Mathematics: A case at Islamic Junior High School (Madrasah) in North Sumatera - MARA SAMIN LUBIS (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2019)
This study aimed to describe students' ability to comprehend the meaning of mathematical vocabulary in one Madrasah in North Sumatera. This research was a qualitative research, with a phenomenology approach. The participants of this research were the seventh-grade students of one Islamic Junior High School (Madrasah) who had high, medium and low ability. The data were collected by using observation, interview and documentation, and were analyzed by using Miles and Huberman models. The results of this study showed that students who had high ability could master three indicators of the ability to understand vocabulary in mathematics; interpreting, summarizing, and explaining. For students who had moderate abilities, they only mastered two indicators of the ability to understand mathematical vocabulary; interpreting and summarizing. For students who had low ability, they only mastered one indicator; interpreting or in other words interpreting vocabulary used in mathematics in their own words.